Comparison of the proliferation, migration and angiogenic properties of human amniotic epithelial and mesenchymal stem cells and their effects on endothelial cells - Wu, Qianqian (Int J Mol Med, 2017)
In vivo studies have shown that amnion-produced growth factors participate in many diseases that involve angiogenesis, re-epithelialization and immunomodulation. Although human amniotic epithelial cells (hAECs) and human amniotic mesenchymal stem cells (hAMSCs) can be obtained from amniotic membranes, there is little information regarding their biological differences. The aim of the present study was to isolate and characterize cells from human amnions, to investigate the biological potential and behavior of these cells on the function of endothelial cells in vivo and in vitro and to examine variations in the expression profile of growth factors in different human amnion-derived cell types. Amnion fragments were enzymatically digested into two cell fractions, which were analyzed by mesenchymal and epithelial cell markers. Human aortic endothelial cells (hAoECs) were cultured with conditioned medium (CdM) collected from hAECs or hAMSCs. We used scratch and Transwell assays to evaluate migration ability; Cell Counting Kit-8 (CCK-8) and cell cycle analysis to evaluate proliferation ability; and a Matrigel tube formation assay to evaluate angiogenesis ability. To detect expression of angiogenesis-related genes, qPCR and enzyme-linked immunosorbent assay (ELISA) analyses were conducted. As stem cells, hAECs and hAMSCs all expressed the stem cell markers SSEA-4, OCT-4 and SOX-2. CdM obtained from hAECs promoted cell migration; CdM obtained from hAMSCs promoted cell proliferation; CdM obtained from hAECs and hAMSCs both promoted angiogenesis in hAoECs. Amnion-derived cells secreted significant amounts of angiogenic factors including HGF, IGF-1, VEGF, EGF, HB-EGF and bFGF, although differences in the cellular expression profile of these soluble factors were observed. Our results highlight that human amniotic epithelial and mesenchymal stem cells, which showed differences in their soluble factor secretion and angiogenic functions, could be ideal cell sources for regenerative medicine.